CONFORMITY TEST OF THE COLLIMATOR BEAM TO X-RAY ON DIAGNOSTIC X-RAY MACHINE AT THE RADIOLOGY INSTALLATION OF ARIFIN ACHMAD HOSPITAL, RIAU - Yoga Saputra; Marido Bisra (Medical Imaging and Radiation Protection Research Journal, 2021)
Conformity test needs to be done in order to avoid deviation of X-rays photo. One of the test is conformity test collimator beam to X-ray. It aims to make sure angle and distance shift does not occur. This study was done at Radiology Installation of Arifin Achmad Hospital, Riau. This study is quantitative with experimental design by using collimator test tool. Tests were be done three times to each big and small focal spot. Based on Ministry of Health No. 1250 on 2009, deviation tolerance limit value is ≤ 2% FFD for conformity test of collimator beam and being ≤ 3° for the center point conformity test. The results of calculations on the small focal spot for X1 + X2 are respectively 2,25 cm, 2,25 cm, and 2,25 cm with an average value of 2,25 cm. In the calculation results of Y1 + Y2 for small focal spots, the results are respectively 0,45 cm, 0,50 cm and 0,50 cm with an average value of 0,48 cm. Then the calculation results on the large focal spot for X1 + X2 obtained results respectively 2,25 cm, 2,20 cm and 2,15 cm with an average value of 2,20 cm. the results of the calculation of Y1 + Y2 for large focal spots, respectively are 0,45 cm, 0,45 cm, and 0,45 cm with an average value of 0,45 cm. This conformity test got the deviation value exceed the tolerance limit on X axis namely of 2.25 cm in average on small focal spots and 2.20 cm on big focal spots. Conformity test results of the beam alignment entirely showed that center point was in a small circle with < 1.5° value. This means there is no deviation of center point which exceed tolerance limit.